The transformation of the insurance industry and road safety by driver safety behaviour telematics. Issue 4 (December 2022) - Ziakopoulos, Apostolos; Petraki, Virginia; Kontaxi, Armira; Yannis, George
Highlights: Trends from recently published research on road safety telematics are discussed. Crash reductions of 20%-43% and harsh event reductions of 10%-52% are reported. Potential for partial (per group) or complete telematics individualization remains. Sensor, data and algorithm developments place transferability vs individualization. Telematics-based research might have biases stemming from data availability. Abstract: In contemporary motorized societies, human factors remain overwhelmingly responsible for road crash occurrence. Urged by considerable technological developments, insurers have integrated telematics to their operations to develop an array of Usage-Based-Insurance (UBI) schemes. The aim of the present research is to expand on the aforementioned topics based on trends from recently published research and discuss the transformation of the insurance industry by driver safety behaviour telematics. Firstly, an overview of the relevant technological advancements is provided, followed by the integration practices of telematics adopted by the insurance industry. A more in-depth examination of the tangible benefits of telematics and driver feedback in road safety is subsequently provided. The paper concludes with a discussion on the future directions of the transformation of the insurance industry, along with the related challenges and limitations.